Masonry patterns' influence on the damage assessment of URM walls: current and future trends - Szabó, Simon (2023)
While the influence of the component strength on the structural behaviour of Historic Masonry Structures (HMS) is relatively well studied, few studies have investigated masonry textures. Such a research gap is due to the actual difficulty of finding parameters that correlate masonry patterns and structural performances. This paper presents a comprehensive review of the existing geometric measures for irregular masonry patterns, highlighting the gaps and possible future trends. Special attention is paid to the Non-destructive Tests (NDT) for surveying masonry textures and algorithms to generate block-based numerical models artificially. Finally, a numerical investigation underlines how masonry textures generated considering quality indexes present more consistent results.